Keperluan program pembangunan profesional (CPD) terhadap profesional juruukur di Malaysia - Alias, Muhammad Nazim (2007)
This study focuses on the importance of CPD to the professional and practice of surveyors. Learning is a life long process. Thus, CPD is describing as a tool to increase and enhance the skills and knowledge of the professional according to the current needs and wants of the industry. There are three objectives of this study, firstly, to identify types of CPDs’ activities preferred by the professional. Secondly, to investigate the effectiveness of CPD towards the enhancement and maintain the skill, knowledge, quality of service as well as work quality and also to reduce professional negligence’s. Thirdly, to investigate each elements of skill, knowledge, service quality and work quality that can be achieved from the CPD activities. The original contribution of this study is firstly, from the knowledge perspective, this will add to the base knowledge of CPD especially to the surveyor profession which is still limited in Malaysia. Secondly, from the perspective of the professional and practice, this study is able to create awareness and understanding of the professional to further enhance the needs and wants of the industry to keep up with the current scenario. This study adopted quantitative (questionnaire survey) and qualitative method (personal interviews). Questionnaire survey was carried out to valuers and quantity surveyors, and thirty one (31) responded. In addition, an interview was also carried out to valuers and quantity surveyors. The key findings of the research demonstrate the significance of CPD to professional surveyors i.e. the valuers as well as the quantity surveyors. It is proven that the CPD is enhancing the skill, knowledge, service and work quality. In addition, the CPD also able to develop self confidence, increase the level of expertise and able to reduce professional negligence. The findings provide insight into; (i) the major elements achieved from a CPD are amendment of act and regulations, current issues, guidelines and new acts, (ii), Types of preferred CPD activities by ranking are seminar, convention, workshop, forum, congress and technical visits, and (iii) CPD is a tool to obtain knowledge and skill which is the basis of a successful professional. It is compulsory for every professional notwithstanding their area and knowledge requirement to enhance their knowledge through educational activities such as CPD, apart from their formal education.